2010
DOI: 10.1186/1741-7015-8-66
|View full text |Cite
|
Sign up to set email alerts
|

What should be done with antisocial personality disorder in the new edition of the diagnostic and statistical manual of mental disorders (DSM-V)?

Abstract: Antisocial personality disorder, psychopathy, dissocial personality disorder and sociopathy are constructs that have generally been used to predict recidivism and dangerousness, alongside being used to exclude patients from treatment services. However, 'antisocial personality disorder' has recently begun to emerge as a treatment diagnosis, a development reflected within cognitive behaviour therapy and mentalisation-based psychotherapy. Many of the behaviour characteristics of antisocial personality disorder ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…As in several previous studies, we found evidence that individuals with ASPD reduced substance use during standard substance abuse treatment [ 1 , 39 ]; in the entire sample, alcohol and drugs composite scores were significantly reduced at the 9-month follow-up. These findings add further support to the view that individuals with ASPD should not be excluded from substance abuse treatment [ 28 , 34 , 39 ]. On the other hand, reductions in substance use generally represented small effect sizes.…”
Section: Discussionsupporting
confidence: 75%
“…As in several previous studies, we found evidence that individuals with ASPD reduced substance use during standard substance abuse treatment [ 1 , 39 ]; in the entire sample, alcohol and drugs composite scores were significantly reduced at the 9-month follow-up. These findings add further support to the view that individuals with ASPD should not be excluded from substance abuse treatment [ 28 , 34 , 39 ]. On the other hand, reductions in substance use generally represented small effect sizes.…”
Section: Discussionsupporting
confidence: 75%
“…Many of the behaviors characteristic of ASPD result in interventions by the criminal justice system(2). A longitudinal study of a cohort of abusers of several classes of drugs identified ASPD as a predictor of criminal behavior(3).…”
Section: Introductionmentioning
confidence: 99%
“…James Phillips and colleagues review what they suggest to be six essential questions in psychiatric diagnosis, and discuss how definitional issues in diagnostic schemas and concepts affect the scope and conduct of psychiatric care, and the social relevance of the field [ 3 ]. In response to proposed changes in the DSM-5, Morten Hesse discusses how revisions in the diagnostic criteria for antisocial personality disorder might lead to more accurate understanding, and improved therapeutics [ 4 ].…”
Section: Editorialmentioning
confidence: 99%